Quercetin and Methotrexate in Combination have Anticancer Activity in Osteosarcoma Cells and Repress Oncogenic MicroRNA-223 - Mohammadi, Erfan; Alemi, Forough; Maleki, Masomeh; Malakoti, Faezeh; Farsad-Akhtar, Nader; Yousefi, Bahman (Drug Research, 2022)
Introduction Osteosarcoma (OS) is one of the most common bone neoplasms in adolescents. Notable short- and long-term toxic effects of OS chemotherapy regimens have been reported. Hence, new chemotherapeutic agents with the ability to potentiate OS chemotherapy drugs and protect non-tumorous tissues are required.Methods Saos-2 cells were treated with Methotrexate (MTX) and Quercetin (Que) (a polyphenolic flavonoid with anti-tumor effects) alone and in combination. MTT assay was performed to investigate the cytotoxicity of the drugs. Moreover, apoptosis-involved genes, including miR-223, p53, BCL-2, CBX7, and CYLD expression were analyzed via qRT-PCR. Annexin V-FITC/PI kit was employed to assess the apoptosis rate.Results The MTT results showed that Que increases MTX cytotoxicity on OS cells. The measured IC50s are 142.3 µM for QUE and 13.7 ng/ml for MTX. A decline in MTX IC50 value was observed from 13.7 ng/ml to 8.45 ng/ml in the presence of Que. Moreover, the mRNA expression outcomes indicated that the combination therapy significantly up-regulates the tumor suppressor genes, such as p53, CBX7, and CYLD, and declines anti-apoptotic genes BCL-2 and miR-223, which can lead to proliferation inhibition and apoptosis inducement. Furthermore, the apoptosis rate increased significantly from 6.03% in the control group to 38.35% in Saos-2 cells that were treated with the combination of MTX and Que.Conclusion Que, with the potential to boost the anticancer activity of MTX on Saos-2 cancer cells through proliferation inhibition and apoptosis induction, is a good candidate for combination therapy.
Keywords: Osteosarcoma; combination therapy; Methotrexate; Quercetin; miR-223; apoptosis